Discovery of a new extreme changing-state quasar with 4 mag variation, SDSS J125809.31+351943.0. (24th November 2020) - Nagoshi, Shumpei; Iwamuro, Fumihide; Wada, Kazuma; Saito, Tomoki
Abstract: We report the discovery of a quasar, SDSS J125809.31+351943.0 (J1258), which brightened in optical wavelengths for 4 mag from 1983 to 2015: one of the largest quasar brightening events so far. The history of optical photometry data of this quasar from the Catalina Real-time Transient Survey and All Sky Automated Survey for Super Novae (ASAS-SN), mid-infrared photometry data from the WISE satellite, and the broad emission line (BEL) flux obtained by spectroscopy of the Sloan Digital Sky Survey shows significant increases between 2003 and 2015. Investigating the Canada–France–Hawaii Telescope photometric observations in 1983 and the United States Naval Observatory B catalogue, which contains data from 1975 and 1969, we found that the source was 4 mag fainter before than at the peak of the recent ASAS-SN photometry. From the history of these data, we identified J1258 as a new changing-state quasar (CSQ). We also performed follow-up spectroscopic observations in 2018 December and 2019 May using the 2 m telescope at the Nishi-Harima Astronomical Observatory. The results show that the continuum flux and the BEL flux decreased to about 50% of their peak. This indicates that J1258 present two changing states for the BEL flux and continuum flux. We argue that J1258's variability, especially its brightening event, can be explained by the propagation of the heating front and the accretion disk state transitions based on the timescale and Eddington ratio variations. The estimated mass of the black hole of J1258 is about an order of magnitude larger than the CSQs found so far. Since both the changing timescale and the size of the accretion disk depend on the black hole mass, the J1258 brightening event can be interpreted as a scaled version of the variability in other CSQs. This suggests that samples of distant quasars with larger black hole masses may contain objects with longer and more severe variations.